(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
Solving inverse equations and higher-order equations is one of the important areas of mathematical analysis and algebra. An inverse equation is an equation that is related to a power or function of a variable and requires finding the value of the variable. Higher-order equations are represented by polynomials of degree two or higher. This topic analyzes methods for solving equations, finding roots using discriminants and formulas, factoring, and graphical approaches. Also, methods for solving higher-order equations using complex numbers and trigonometric functions are considered. Along with theoretical foundations, problem-solving strategies and practical applications serve to strengthen mathematical knowledge. The topic is widely used in the fields of scientific research and applied mathematics.